Relationship of Roof Areas and Rainwater Harvesting Tank Sizes for Squatter at Sion Village, Sarawak, Borneo Island - King Kuok, Kuok; Po Chan, Chiu; Mei Yun, Chin; Rezaur, Rahman; Khairul Anwar, Mohamad Said (Scientific Research Publishing Inc., 2025)
The rainwater harvesting system (RWHS) is widely recognized as a viable water source for drinking and non-drinking purposes, helping mitigate stormwater runoff. In 2019, an RWHS was installed in Sion village, a squatter that lacks connection to the potable water supply grid, with each household receiving a standardized tank size of 1.816 m3. However, the optimal tank size for rainwater harvesting can vary depending on roof sizes and water demands. Since the roofs in Sion village vary in size, this study aims to investigate the relationship between roof size and tank size, considering reliability percentage and installation cost. This investigation utilized the Tangki NAHRIM software and analyzed six different tank sizes: 0.682 m3, 1.136 m3, 1.589 m3, 1.816 m3, 2.270 m3, and 2.724 m3, across roof sizes of 60 m2, 85 m2, 100 m2, 160 m2, and 200 m2. The study set a benchmark for reliability between 80% and 89%. The reliability percentage gradually improves with increasing roof and tank sizes, but the installation cost increases as well. A minimum tank size of 0.682 m3 was found sufficient to achieve a reliability of 85.02% for roof size of 85 m2, 85.57% for 100 m2, 88.84% for 160 m2, and 90.07% for 200 m2. Similar reliability percentage increment trends were observed for the tank sizes of 1.136 m3, 1.589 m3, 1.816 m3, 2.270 m3, and 2.724 m3. A tank size of 1.136 m3 provides a reliability percentage of 95.50% for a roof size of 60 m2, making 1.136 m3 the minimum optimal tank size for this roof area. Results revealed that all the investigated roof sizes achieved higher reliability percentages than 85%, starting from the tank size of 1.136 m3